Significant Decreasing Trend in Low Back Injuries in a Beverage Company. Issue 10 (October 2018) - Kalia, Nimisha; Lavin, Robert A.; Leung, Nina; Yuspeh, Larry; Bernacki, Edward J.; Tao, Xuguang (Grant)
Abstract : Background: Work-related injuries in the U.S. have steadily declined over the past three decades. Objective: The aim of this study was to compare trends of the most frequently injured body parts from a beverage company over an 8-year study period (2008 to 2015). Method: Work-related injury claims with more than 3 days of missed work ( N  = 20, 203) were classified into body part groups, including low back, knee, shoulder, and all other(s). Descriptive statistics and linear models were used to evaluate trends over time. Results: The total number of injuries decreased from 6.57 per 100 to 3.79 per 100 employees from 2008 to 2015. Proportion of low back injuries decreased from 22.0% to 15.4% ( P  < 0.001) over the study period. Proportionally, knee(s), shoulder(s), and all other injuries increased, but the changes did not reach statistical significance. Conclusion: Low back injuries decreased at a faster rate than knee, shoulder, and all other injuries.